Label-free enrichment of human blast cells from whole blood for leukemia monitoring - Yatian Fu; Shangjie Zou; Bee Luan Khoo (STAR Protocols, 2022)
Summary: Liquid biopsy is an alternative to invasive bone marrow biopsy for leukemia detection and management. However, no robust technology is available for enriching leukemic blast cells from the blood. Here, we present a simple and effective protocol for vigorous enrichment of blast cells from whole blood using a one-step microfluidic blast cell biochip (BCB) that exploits distinct cell mechanical properties between diseased and healthy leukocytes. The BCB system achieves higher sensitivity than flow cytometry in detecting blasts.For complete details on the use and execution of this protocol, please refer to Khoo et al. (2019). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.